Avaliação da ingestão de microplásticos em microcrustáceos da Represa de Barra Bonita (Rio Tietê, SP - Brasil) - Nascimento, Fernanda Thais Fernandes (Universidade Federal de São Carlos, 2024)
Human activity is responsible for the production of a large part of the microplastics present in marine and freshwater environments, which can be ingested by various organisms, including zooplankton. The present study aimed to determine the dry weight values ​​of microplastics (mp) ingested by microcrustaceans in a eutrophic and polluted reservoir (Barra Bonita Reservoir, Tietê River). Sixty zooplankton samples were collected using a conical plankton net with a 68μm mesh opening during March 2023. Before fixation in 4% formalin, commercially cold carbonated water was used to anesthetize the organisms, avoiding regurgitation. The organisms were identified at the specific level under a stereoscope and microscope. For digestion, three concentrations of KOH (10, 15 and 20% w/v) were tested in an oven at 60°C for 1h in batches of 10 specimens for each species. After verifying the best digestion results among the concentrations, it was decided to use 10% and 15% in cladocerans and 20% in copepods. Using a precision analytical balance (Sartorius 215) with 6 places, the organisms with mp were weighed individually after drying, and then the mp was removed and weighed separately. 11,267 specimens of 13 species were digested, namely: Daphnia gessneri (Herbst, 1967), Diaphanosoma birgei (Korinek, 1981), Moina minuta (Hansen, 1899), Ceriodaphnia cornuta (Sars, 1886), Notodiaptomus iheringi (Wright, 1935), Notodiaptomus cear ensis (Wright, 1936), Mesocyclops meridianus (Kiefer, 1926), Metacyclops mendocinus (Wierzejski, 1892), Thermocyclops decipiens (Kiefer, 1929), Acanthocyclops robustus (Sars, 1863), Microcyclops anceps (Richard, 1897), Mesocyclops ogunnus (Onabamiro, 1957) and Mesocyclops longisetus (Thiébaud, 1912), divided into 1725, 1010, 120, 1001, 1020, 200, 120, 150, 200, 1001, 1005, 165 and 150 individuals, respectively. Among the copepods, 2000 and 1500 organisms of Calanoida and Cyclopoida, respectively, were digested in larger batches and without identification to the species level. Among all the digested organisms, four mps particles were found in four specimens of D. gessneri, and the dry weights of the organisms and microplastics were obtained individually. Ingested microplastics were not found in any other species. The first hypothesis, that all groups ingest the particles, was partially proven, having been found only in the cladoceran D. gessneri. The second hypothesis, that the larger the individual, the larger the microplastic particles, was proven, although we obtained few values ​​in a large number of digested specimens. Although microplastics were found in the microcrustaceans, the percentage is minimal when compared to the total number of specimens analyzed, even in a polluted reservoir, lower than the percentage found in a marine environment.
Evaluation of microplastic ingestion in microcrustaceans from the Barra Bonita Reservoir (Tietê River, SP - Brazil)
Keywords: Poluição; Microplásticos; Biomassa; Zooplâncton; Ingestão; Pollution; Microplastics; Biomass; Zooplankton; Ingestion; CIENCIAS BIOLOGICAS::ECOLOGIA